Wrongfully Convicted Women: Before, During, and After Wrongful Conviction - Pacholski, Casandra; Anderson, Gail S. (The Wrongful Conviction Law Review, 2025)
In the past three decades, North America has exonerated over 3,400 innocent people of crimes they did not commit—with nearly 300 of those exonerees being women. Recent years have seen a 700% increase in female incarceration, which could influence future rates of wrongful convictions among women as well. The existing literature on wrongful conviction disproportionately focuses on male exoneree experiences and stories, leaving female exoneree needs and experiences entirely unaccounted for. The following review identifies the relevant literature pertaining to the lived experiences of mothers, exonerees, and incarcerated women to address the gaps in the wrongful conviction literature and inform future research projects. Evidenced by this review is that systematic differences are leading to the wrongful conviction of women, women experience different pains of imprisonment and may be at a disproportionate risk of mental and physical health complications due to their wrongful conviction and incarceration. Future research must focus on the unique lived experiences of female victims of wrongful convictions to understand the mechanisms underlying their convictions, and their unique experiences of wrongful conviction, incarceration, re-entry, and victimization, to adequately inform policy and help in their re-entry and rehabilitation.